REVEALING TEACHER’S AND STUDENTS’ STRATEGY TOWARDS STUDENTS’ ANXIETY IN SPEAKING ENGLISH AT MA DDI ALLIRITENGAE MAROS - Andi Mar'ah Muthmainnah; Novalia Tanasy; Nurul Fachrunnisa (Wiralodra English Journal, 2026)
This study aimed to explore the strategies applied by teachers and students in reducing anxiety in speaking English at MA DDI Alliritengae Maros, as many students experience fear and lack of confidence when speaking English in the classroom, which limits their participation and speaking performance. This study employed a qualitative research method using semi-structured interviews and classroom observations as data collection techniques. The collected data were analyzed with data reduction, data display, and conclusion drawing. Participants consist of one English teacher and nine 10th-grade senior high school students. The results indicated that teachers employ encouraging regular speaking practice, providing appreciation and motivation, enriching vocabulary through memorization methods, using interactive methods like role-playing and group work, and offering flexibility in language use during lessons. Meanwhile, students developed personal strategies such as cultivating positive thoughts, memorizing vocabulary, performing relaxation techniques, shifting their gaze, choosing to remain silent, and using simple physical techniques to calm themselves.